2014
DOI: 10.4103/2141-9248.139325
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between CD4+ counts and the presence of oral lesions in human immunodeficiency virus positive women in Nigeria

Abstract: Background:Oral lesions are common findings in human immunodeficiency virus (HIV) infection. The main factor associated with the development of oral lesions is damage to the immune system, specifically loss of CD4+ lymphocytes, which are involved in cell-mediated immunity.Aim:This study was aimed to determine the association of oral lesions in HIV/acquired immune deficiency syndrome women patients with the level of immune suppression as measured by the CD4+ counts.Subjects and Methods:This was a prospective cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies have reported on strong associations between HIV-1 infection and oral mucosal lesions and periodontal disease [8][9][10][11]. Moreover, the prevalence of oral lesions seems to increase with increasing level of immune suppression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported on strong associations between HIV-1 infection and oral mucosal lesions and periodontal disease [8][9][10][11]. Moreover, the prevalence of oral lesions seems to increase with increasing level of immune suppression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two forms of oral candidiasis were identified in this study: erythematous and pseudomembranous, which are two key prognostic indicators in HIV infection and progression to AIDS [ 28 , 29 ]. Both forms of oral candidiasis were identified mainly among patients with severe immune suppression, which is an important predictor of opportunistic infections among PLHIV [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,15 Oral melanotic hyperpigmentation could be used as markers of immunosuppression depicted by CD4+ counts < 200 cells/ml in HIVpositive patients. 16 It is unknown whether structural proteins of HIV can stimulate melanocyte activity directly to upregulate their melanin biosynthesis. It is possible that HIV-associated mucosal hyperpigmentation may fortuitously represent a local protective immune reaction against subclinical oral infections and concomitant inflammatory processes.…”
Section: Addison's Diseasementioning
confidence: 99%